2021
DOI: 10.2147/opto.s305927
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative Observation of a Macular Holes Using Optical Coherence Tomography

Abstract: Purpose This study aimed to observe intraoperative changes in macular hole (MH) form using intraoperative optical coherence tomography (iOCT). Methods A total of 10 eyes from 10 patients with MH who underwent vitrectomy using iOCT from May 2015 to October 2015 at the Yamagata University Hospital were retrospectively evaluated. Accordingly, 25-gauge pars plana vitrectomy using iOCT with internal limiting membrane (ILM) peeling and sulfur hexafluoride gas tamponade was pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…These results allow us to expect that more significant intraoperative changes in FTMH morphology might reflect an increased hole laxity and indicate an increase in the probability of FTMH closure. Their results might be considered only partially coherent with the subsequent study by Riazi-Esfahani et al [ 27 ] and Nishitsuka et al [ 17 ], who also found a decrease in the inner area of the FTMHs post-ILM peeling, whereas they found no increase in the base diameter. Furthermore, Nishitsuka et al described that the mean minimum diameter of FTMH decreased significantly after fluid–gas exchange, highlighting the importance of gas-surface tension, even though the patients did not demonstrate intraoperative FTMH closure.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…These results allow us to expect that more significant intraoperative changes in FTMH morphology might reflect an increased hole laxity and indicate an increase in the probability of FTMH closure. Their results might be considered only partially coherent with the subsequent study by Riazi-Esfahani et al [ 27 ] and Nishitsuka et al [ 17 ], who also found a decrease in the inner area of the FTMHs post-ILM peeling, whereas they found no increase in the base diameter. Furthermore, Nishitsuka et al described that the mean minimum diameter of FTMH decreased significantly after fluid–gas exchange, highlighting the importance of gas-surface tension, even though the patients did not demonstrate intraoperative FTMH closure.…”
Section: Discussionsupporting
confidence: 83%
“…Nishitsuka et al aimed at observing intraoperative changes in FTMH morphology using iOCT [ 17 ]. They included 10 eyes from 10 patients undergoing surgical treatment for FTMH detected intraoperatively by the Rescan™ 700 system (Carl Zeiss Meditech, Oberkochen, Germany).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in a recent report by Nishitsuka and colleagues, hole diameter was measured through iOCT at different surgical stages, showing a decrease after ILM peeling and a further reduction after gas tamponading, probably due to the centripetal surface tension force between the retina and the gas bubble [39]. The ability of iOCT to observe the macular hole changes intraoperatively may also affect the recommendations for postoperative face-down positioning protocols.…”
Section: Clinical Applications In Vitreoretinal Surgery: Macular Holementioning
confidence: 99%